Resistome analysis of bloodstream infection bacterial genomes reveals a specific set of proteins involved in antibiotic resistance and drug efflux. Issue 3 (31st July 2020) - Oliveira, Willian K; Ferrarini, Mariana; Morello, Luis G; Faoro, Helisson
Abstract: Bacterial resistance to antibiotics is a global public health problem. Its association with bloodstream infections is even more severe and may easily evolve to sepsis. To improve our response to these bacteria, it is essential to gather thorough knowledge on the main pathogens along with the main mechanisms of resistance they carry. In this paper, we performed a large meta-analysis of 3872 bacterial genomes isolated from blood samples, from which we identified 71 745 antibiotic resistance genes (ARGs). Taxonomic analysis showed that Proteobacteria and Firmicutes phyla, and the species Klebsiella pneumoniae and Staphylococcus aureus were the most represented. Comparison of ARGs with the Resfams database showed that the main mechanism of antibiotic resistance is mediated by efflux pumps. Clustering analysis between resistome of blood and soil-isolated bacteria showed that there is low identity between transport and efflux proteins between bacteria from these environments. Furthermore, a correlation analysis among all features showed that K. pneumoniae and S. aureus formed two well-defined clusters related to the resistance mechanisms, proteins and antibiotics. A retrospective analysis has shown that the average number of ARGs per genome has gradually increased. The results demonstrate the importance of comprehensive studies to understand the antibiotic resistance phenomenon.